Adolescents amid the COVID-19 pandemic: a prospective study of psychological functioning - Ieva Daniunaite; Inga Truskauskaite-Kuneviciene; Siri Thoresen; Paulina Zelviene; Evaldas Kazlauskas (BMC, 2021)
Abstract Background The spread of coronavirus disease (COVID-19) and the accompanying countermeasures can significantly impact the wellbeing of adolescents. There is a lack of longitudinal studies that can shed light on potential social, emotional, and behavioral development in adolescents. We aimed to identify potential changes in adolescent psychosocial functioning from pre-pandemic to peri-pandemic assessment, and secondly, to identify specific patterns of change. Methods This longitudinal study was based on a Lithuanian community sample of 331 adolescents aged 12-16 at T1 (M  =  13.87, SD  =  1.59). T1 data collected before the pandemic (March-June, 2019) was compared with T2 data collected during the COVID-19 outbreak (October 2020). Psychosocial functioning was assessed by The Strengths and Difficulties Questionnaire (SDQ). Multivariate latent change modeling and latent class change approaches were used to identify patterns of change. Results We found a small but significant increase in hyperactivity/inattention, emotional symptoms, but also prosocial behavior from before to during the pandemic, even adjusting for resilience, lifetime abuse experience, and socio-demographic situation. Three change profiles were identified in the latent change analysis: (1) a majority (70.7%) experienced a significant increase in psychosocial problems; (2) a smaller sub-group (19.6%) with increased peer problems only; (3) a small group (9.7%) showing no negative change and an increase in prosocial behavior. Conclusions The study found a significant negative impact of the COVID-19 pandemic on mental health in the majority of adolescents, as well as indications of positive social development in a small group. These findings highlight the importance of identifying and supporting adolescents in the time of the pandemic more effectively. Accumulating knowledge about human responses to the coronavirus, particularly in young people, is pivotal to societal preparedness for future pandemics.